Word-Formation Description and Morphological Status of Intensifiers in Norwegian - Skommer, Grzegorz (Folia Scandinavica Posnaniensia, 2007)
The author analyses the morphological status of some Norwegian prefixes and first-words of compounds which convey the semantic feature of intensification: The status is hard to establish due to the incessant process of transition of independent words into affixes. After discussing the complex nature of word-formation analysis the author puts forward a hypothesis that the primary concern of word-formation studies should be meaning.